Conscientious objection in Spanish podiatrists students: a questionnaire survey - López López, Daniel; De la Campa Portela, Rosa Mary; Losa Iglesias, Marta Elena; Ramos Galván, José; Munuera Martínez, Pedro Vicente; García Sánchez, Matilde; Becerro de Bengoa Vallejo, Ricardo (Acta Bioethica, 2016)
Objective: To explore attitudes towards conscientious objections among podiatrists students in Spain. Methods: Podiatrists students at University of A Coruña, King Rey Juan Carlos University, University of Sevilla and Complutense University of Madrid were emailed a link to complete an anonymous online questionnaire, hosted by an online survey company. A total of 432 podiatrists students responded. Results: Nearly half of the students in this survey stated that they believed in the right of podiatrist to conscientiously object to any procedure. Demand for the right to conscientiously object is greater in Roman Catholic podiatrists students when compared with other groups of religious podiatrists students. Discussion: Examining patients and podiatric treatments continues to be controversy issues among podiatrists students and this may contribute to the looming crisis in podiatry services over next years. This project sheds some light on how future podiatrist view some of their ethical rights and obligations. Using empirical evidence, it reveals that conscientious objection is an issue in the Spain podiatrists student body today. These data could help anticipate problems that may arise when these podiatrists students qualify and practice podiatry in the community. Conclusion: Clearer guidance is needed for podiatrists students about the issue of conscientious objection at podiatry school.